Dawr Jam‘iyah al-Ṭalabah al-Islāmīyīn fī Ḥarakah al-Jayl 66 al-Indūnīsīyā - AS, Saifullah (Studia Islamika, 1995)
The evnt which occurred in the middle of the 1960s formed a significant turning point in the course of Indonesian history. The Indoensian Community Party (PKI) which dominated the Indonesian political scene was toppled as aresult of its abortive coup d'etat. These events led to the emrgence of a new political order, which was later called the New Order era (masa Orde Baru). The term of "New Orde" was used to describe a new phase of Indonesian political life which ended the previous model of political order, that of the Old Order (orde Lama).DOI: 10.15408/sdi.v2i3.830